2012
DOI: 10.2217/rme.12.58
|View full text |Cite
|
Sign up to set email alerts
|

Inner Ear Progenitor Cells can be Generated in Vitro from Human Bone Marrow Mesenchymal Stem Cells

Abstract: This study demonstrates that hMSCs can be driven to express key genes found in the otic lineages and thereby promotes their status as candidates for regenerative therapies for deafness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…A number of recent studies have shown that pluripotent stem cells can be differentiated into progenitor and HC‐like cells under different adherent culture conditions. However, the methods applied to these studies have relied upon co‐culturing cells with tissues from the developing inner ear (Boddy et al ., ; White et al ., ), the chicken utricle (Oshima et al ., ) or using conditioned medium that contained stromal factors (Ouji et al ., ). For these reasons, it is questionable whether these experiments are suitable for assessing the grafting capacity of the inner ear progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent studies have shown that pluripotent stem cells can be differentiated into progenitor and HC‐like cells under different adherent culture conditions. However, the methods applied to these studies have relied upon co‐culturing cells with tissues from the developing inner ear (Boddy et al ., ; White et al ., ), the chicken utricle (Oshima et al ., ) or using conditioned medium that contained stromal factors (Ouji et al ., ). For these reasons, it is questionable whether these experiments are suitable for assessing the grafting capacity of the inner ear progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in the understanding of molecular mechanisms related to HC production and stem cell technology have raised the possibility that HC‐like cells might be generated from both embryonic and adult stem cell sources (Savary et al ., ; Oshima et al ., ; Boddy et al ., ; Ouji et al ., ; Koehler et al ., ; Ronaghi et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, otic progenitors can be induced from pluripotent stem cells by activating FGF signaling with ligands involved in the generation of the placode in vivo , such as FGF3 and FGF10 (Chen et al, ). Alternatively, inner ear progenitors can be generated in vitro , from other stem cell populations, circumventing the above‐described procedure of stepwise addition of signaling molecules (Boddy et al, ). Human mesenchymal stem cells were cultured in media which previously has been used to culture human fetal auditory cells.…”
Section: Focussing On the Inner Earmentioning
confidence: 99%
“…Other authors maintain that putative cochlear SCs may derive from the mesenchymal SCs (MSCs) reservoir located in the inner ear stroma underlying the epithelial tissue [41]. Although it remains unclear, some studies have shown that MSCs are able to differentiate in vitro in both HClike cells and neurons [42,43].…”
Section: Cochlear Scsmentioning
confidence: 99%